The Teaching Quality Evaluation System for Teachers of Universities Under Sichuan Province - Zhaoheng, Du; Howattanakul , Sutida; Chanphong, Somsak (Journal of Roi Kaensarn Academi, 2024)
The result of this research can be to mechanically guide people towards evaluating items and one-sided pursuit of external value goals, with its function limited to judging value, rather than discovering value. This also limits the value construction of higher education, damages the vibrant spiritual atmosphere of universities, and is not conducive to the formation of the unique internal cultural heritage of universities themselves. The objectives of this study were：(1) to explore the components and indicator of the evaluation system of teaching quality of teachers in colleges and universities under the province of Sichuan.(2) to put forward the guiding ideology of teaching quality evaluation of teachers in provincial colleges and universities in Sichuan Province. The study was a mixed methodology study. The population was educational administrators and teachers, totaling 4620. The sample size was 539 teachers and administrators using a stratified random sampling technique determined according to the Krejcie and Morgan table (1970). The data collection instruments were semi-structured interview form and five-point scale questionnaire and Focus Group Discussion form. Statistical quantities used for data analysis included frequency, percentage, mean, and standard deviation, and Exploratory Factor Analysis and content analysis were employed. The results of the study showed that; the results of the study showed that (1) Teaching quality evaluation system for teachers in colleges and universities under the Sichuan Province, there are 3 components consist of Perceived quality of teaching, Perceived Teaching Input, Perception of the teaching environment. (2) There are 5 guiding of teaching quality evaluation of teachers in provincial colleges and universities in Sichuan Province, consist of (1) Change the way of education evaluation (2) Enhance the level of teachers career mechanism.(3) Optimising educational resources informatization. (4) Strengthen international exchanges and (5) Improve the quality of education environment.